A framework for integration of Madrasah into the basic education curriculum - Arsad, Nefertari Al-Raschid (2007)
This study was inspired by Department of Education initiatives to integrate the Madrasah into Philippine education. Methodologies employed were key informant interviews of DepEd officials, review of DepEd and other literature to determine the integration rationale and curriculum, analysis of the framework according to Islamic education standards, case studies of two schools practicing Madrasah integration, in-depth interviews of selected Muslim scholars, and a review of literature on multicultural education to cull relevant principles.It was found that the framework used in the integration does not conform to Islamic education standards due to severe lack of content, poor organization and articulation of skills and concepts, poor contextual treatment of subject matter and contentious additions of units of studies. The alternative framework will provide Muslim learners core Islamic education subjects within the Philippine curriculum.
Thesis (M.A. Curriculum Studies)--University of the Philippines Diliman.
Keywords: Muslims -- Education -- Philippines; Education -- Philippines -- Curricula